2022
DOI: 10.15517/nat.v16i2.52922
|View full text |Cite
|
Sign up to set email alerts
|

Composición bromatológica de ensilados de leguminosas con diferentes fuentes de carbohidratos

Abstract: El objetivo de este estudio fue determinar las características nutricionales de mezclas frescas y ensiladas, elaboradas a partir de leguminosas y cuatro fuentes de carbohidratos. El experimento fue realizado entre los años 2015 y 2016. Se utilizó un diseño factorial al azar, donde se combinaron cuatro especies de leguminosas (Vigna unguiculata, Arachis pintoi, Cratylia argentea, Erythrina poeppigiana) y cuatro fuentes de carbohidratos (melaza de caña de azúcar, pulpa de cítricos deshidratada, maíz molido y fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…However, there is limited information available on the nutritional quality of these combinations in tropical and subtropical climates. Likewise, in the search for alternatives for the conservation of legume forage, some additives such as molasses have been tested (López-Herrera et al, 2022), however, so far there are few publications related to its application in soybean forage silage. It has been reported that, for the conservation of corn and soybean forage, the treatment that had the highest nutritional quality without seriously compromising the silage process was the combination with 60% corn and 40% soybeans (Figure 3; Garay-Martínez et al, 2021); whereas, for proper preservation of soybean forage through silage, 66% molasses should be applied, either in layers of 10 or 20 cm; and this ensures the proper fermentation process, having a pH in the silage that ranges between 3.8 and 4.0 (Figure 8.3; Garay-Martínez et al, 2023).…”
Section: Forage Conservationmentioning
confidence: 99%
“…However, there is limited information available on the nutritional quality of these combinations in tropical and subtropical climates. Likewise, in the search for alternatives for the conservation of legume forage, some additives such as molasses have been tested (López-Herrera et al, 2022), however, so far there are few publications related to its application in soybean forage silage. It has been reported that, for the conservation of corn and soybean forage, the treatment that had the highest nutritional quality without seriously compromising the silage process was the combination with 60% corn and 40% soybeans (Figure 3; Garay-Martínez et al, 2021); whereas, for proper preservation of soybean forage through silage, 66% molasses should be applied, either in layers of 10 or 20 cm; and this ensures the proper fermentation process, having a pH in the silage that ranges between 3.8 and 4.0 (Figure 8.3; Garay-Martínez et al, 2023).…”
Section: Forage Conservationmentioning
confidence: 99%